A festa de nossa senhora de Nazaré no rio Caripetuba: uma análise das mudanças e permanências - GONÇALVES, Silvia Letícia Lobato (2022)
This work aimed to investigate the changes and permanences that occurred in the festivity of Nossa Senhora de Nazaré in the locality of Rio Caripetuba, rural space (islands) in the municipality of Abaetetuba-PA. The festival takes place on the third Sunday of the month of October and is expected by the faithful devotees of Our Lady throughout the year, featuring a period in which joint efforts occur, prevailing relations of reciprocity and devotion to the image, marking a very common religious culture in the interior of the region. Amazonian with beliefs inherited from a historically constituted cultural hybridity, but which has been gradually questioned or even devalued by new generations due to the current moment based on new models of religiosity. In this way, we try to question in view of the changes in the way the celebration takes place, what remained as a traditional element of devotion. To reach the answer, an analysis of popular Catholicism in Brazil and more particularly in the Amazon, as well as within the community locus of the research, was carried out. I also tried to understand from open interviews the origin of the image, how the novenas were organized in preparation for the party, the litany group, the pilgrimages in other communities, what was the tradition of the oratories in the homes, the symbolism of the mantle, the flag. To carry out this work, qualitative research methodology with observation and application of interviews and semi-structured questionnaires was used as methodology, and seven people were interviewed, five elderly and two adults, one of these adults was already a community coordinator and has an oratory in his house and the other is the current coordinator, the elderly are people who have always worked in the community, being coordinators as well as assiduous participants, who have always donated their work for the community, one of them is one of the heirs of the image. So I had the intention of interviewing them because they had such good involvement and work within the community of many years ago, I tried to carry out an analysis of the past and the present through them. Also used as a resource was a notebook for taking notes, a cell phone for recordings and photographic images. We managed to get results in the work, that the party remains with some modifications, such as, the lack of a group of revelers, the withdrawal of pilgrimages in other communities, the extinction of alcoholic beverages, which according to the interviews, was the best change.